1999
DOI: 10.1016/s1074-5521(99)80048-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of functionally diverse 2,6,9-trisubstituted purine libraries as CDK inhibitors

Abstract: 2,6,9-Trisubstituted purines have various and potent biological activities, despite high concentrations of competing endogenous purine ligands in living cells. Purine libraries constitute a versatile source of small molecules that affect distinct biochemical pathways mediating different cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
228
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 273 publications
(236 citation statements)
references
References 18 publications
7
228
0
1
Order By: Relevance
“…Olomoucine has been reported to enhance the induction of apoptosis by a DNA damaging agent mitoxantrone without a ecting cell cycle distribution (Ongkeko et al, 1995). Chang et al (1999) synthesized a variety of purine derivative olomoucine-or roscovitine-related Cdk inhibitors by combinatorial chemistry and studied their e ects on cell cycle distribution and their ability to induce apoptosis. One of these inhibitors designated 209 induced apoptosis without a ecting overall cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Olomoucine has been reported to enhance the induction of apoptosis by a DNA damaging agent mitoxantrone without a ecting cell cycle distribution (Ongkeko et al, 1995). Chang et al (1999) synthesized a variety of purine derivative olomoucine-or roscovitine-related Cdk inhibitors by combinatorial chemistry and studied their e ects on cell cycle distribution and their ability to induce apoptosis. One of these inhibitors designated 209 induced apoptosis without a ecting overall cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,22,32,33 In this study new aspects of the structure-activity relationship became apparent, including correlation with effect on cell proliferation.…”
Section: Structure-activity Relationshipmentioning
confidence: 99%
“…We report here that indirubins are very potent inhibitors (IC 50 values in the 5-50 nM range) of glycogen synthase kinase-3␤ (GSK-3␤). This kinase is an essential element of the WNT signaling pathway (29).…”
mentioning
confidence: 99%
“…The kinase selectivity study showed that indirubins have a strong affinity for CDKs (IC 50 values in the range of 50 -100 nM) (25). Nevertheless, they are not totally devoid of activity toward a few kinases (IC 50 values in the 1-10 M range) (25). This rather loose selectivity, when compared with the high specificity of purine inhibitors of CDKs, led us to continue to investigate the selectivity of indirubins as kinase inhibitors.…”
mentioning
confidence: 99%